Utilization of the National Building to Increase Regional Original Income of Sungai Penuh City - Asti Harkeni; M.Rialdi Syaputra (Balitbangda Provinsi Jambi, 2022)
Sungai Penuh City is a city resulting from the division that has many regional assets that have not been identified and managed properly. One of them is Gedung Nasional, which is a regional asset as a result of the handover from Kerinci Regency in 2021. The purpose of the research is to formulate a model for the utilization of Gedung Nasional as a multi-purpose building and determine the strategy for optimizing the utilization of Gedung Nasional to increase the Regional Original Income of Sungai Penuh City. This study uses a mixed method approach through observation, documentation and interviews with the government, community leaders and filling out a purposive sampling questionnaire. The data analysis tool uses the Analytical Hierarchy Process (AHP) with a Saaty scale approach starting from a weighted value of 1 to 9. The results of the study obtained that the optimization strategy for the utilization of Gedung Nasional to increase the Regional Original Income of Sungai Penuh City is (1) improving/adding facilities and services, (2) providing incentives to levy collectors/managers, (3) requiring the use of Gedung Nasional facility as a standard for Sungai Penuh City physical activity, (4) improving the legal/regulatory system, (5) establishing criteria and evaluating the object of retribution for cooperation with other parties. third parties.